The secret of the Hardy boys : Leslie McFarlane and the Stratemeyer Syndicate - Greenwald, Marilyn S. (Ohio University Press, 2004)
"The author of the Hardy Boys mysteries was, as millions of readers know, Franklin W. Dixon. Except that there never was a Franklin W. Dixon. He was the creation of Edward Stratemeyer, the founder of a children's book empire that also published the Tom Swift, Bobbsey Twins, and Nancy Drew series. The Secret of the Hardy Boys: Leslie McFarlane and the Stratemeyer Syndicate recounts how a newspaper reporter with dreams of becoming a serious novelist first brought to life Joe and Frank Hardy, who became two of the most famous characters in children's literature." "Leslie McFarlane, better known as Franklin W. Dixon, wrote twenty of the first twenty-four Hardy Boys mysteries for about $100 per book. He relished the anonymity demanded by the Stratemeyer Syndicate, admitting his authorship of the books to no one, not even his children - his son pried the truth out of him years later. He wrote about the exploits of the Hardy Brats, as he called them, from 1927 to 1947, work that put food on the McFarlane table and allowed him the independence of a professional writer." "A best-selling author, McFarlane never made a penny more from the Hardy Boys series than the flat fee he was paid for each book. Having signed away all rights to the books, McFarlane never shared in the wild financial success of the series." "This book is a story of talent and character as well as of the Stratemeyer Syndicate and the growth and development of children's literature in North America."--Jacket.